TRANSGENDER COMMUNITY ACTIVITIES AND THEIR MARRIAGE CONCEPT IN YOGYAKARTA - Rauf, Muta’Ali (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2013)
Transgender have been considered as someone who always marginalized in their life, so they always get moral discrimination, social and even religion. Development of the transgender community in Yogyakarta is currently getting a response from various groups, namely the general public, religious leaders, sociologists and psychologists. As for job transsexual Kebaya NGOs joined in Yogyakarta, located in very small scope, include: ngamen, nyebong, salon and sewing. It was done since the transvestites are out of work in the formal sector. The concept of marriage in transgender community in Kebaya NGOs does not have clear rules because there is no basis or guidelines. Same-sex marriage in Indonesia is not recognized legally as well as normative, so the concept of transsexual marriage does not exist according to Islamic law. Kebaya NGOs consider that the rules about marriage in Indonesia violate the human rights, because it does not facilitate and accommodate the same-sex marriage.[Waria selama ini dianggap sebagai sosok yang selalu termarginalkan di dalam kehidupannya, sehingga mereka selalu mendapatkan diskriminasi baik moral, sosial, maupun agama. Perkembangan komunitas waria di Yogyakarta saat ini mendapat respon dari berbagai kalangan, yaitu masyarakat umum, tokoh Agama, Sosiolog, dan Psikolog. Adapun pekerjaan Waria Yogyakarta yang tergabung dalam LSM Kebaya, berada dalam skala yang sangat kecil meliputi : Ngamen, Nyebong, salon dan menjahit. Hal itu dikerjakan semenjak waria tidak mendapat pekerjaan dalam sektor formal. Konsep perkawinan dalam komunitas waria di LSM Kebaya belum mempunyai aturan yang jelas karena tidak ada landasan atau pedomannya. Perkawinan sesama jenis di Indonesia tidak mendapatkan pengakuan secara yuridis maupun normatif, sehingga konsep perkawinan waria tidak eksis menurut Hukum Islam. LSM Kebaya menganggap bahwa peraturan tentang perkawinan di Indonesia melanggar hak asasi manusia, karena tidak memfasilitasi perkawinan sesama jenis.]